2018
DOI: 10.4097/kjae.2018.71.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to systematic review and meta-analysis

Abstract: Systematic reviews and meta-analyses present results by combining and analyzing data from different studies conducted on similar research topics. In recent years, systematic reviews and meta-analyses have been actively performed in various fields including anesthesiology. These research methods are powerful tools that can overcome the difficulties in performing large-scale randomized controlled trials. However, the inclusion of studies with any biases or improperly assessed quality of evidence in systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
272
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(288 citation statements)
references
References 35 publications
0
272
0
16
Order By: Relevance
“…Due to the identification of only 1 controlled study, and according to the methodological recommendation against performing a meta-analysis of observational studies without a control group, (15) information regarding outcomes reported by each study was presented in tables for comparison without a statistical assessment.…”
Section: Data Synthesismentioning
confidence: 99%
“…Due to the identification of only 1 controlled study, and according to the methodological recommendation against performing a meta-analysis of observational studies without a control group, (15) information regarding outcomes reported by each study was presented in tables for comparison without a statistical assessment.…”
Section: Data Synthesismentioning
confidence: 99%
“…Systematically reviewing the published literature means answering a defined research question by gathering, appraising and synthesizing all empirical evidence that fits pre‐specified eligibility criteria (Systematic reviews and meta‐analyses: a step‐by‐step guide). A meta‐analysis is the use of statistical methods to quantify and summaries the results of these studies (Ahn & Kang, Systematic reviews and meta‐analyses: a step‐by‐step guide). Informed by the importance of non‐typhoidal Salmonella enterica in public health and to identify gaps in evidence, the main research questions addressed by the present systematic review were (a) “what is the pooled prevalence of non‐typhoidal Salmonella in human populations in the MENA region?”, and (b) what are the most common human Salmonella serotypes in the MENA region?’.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment failure rates, mortality rates, 3-and 5-year overall and disease-free survival rates were extracted and entered in the REVMAN 5.2 software. For dichotomous variables, odds ratios with their 95% confidence intervals were calculated with Mantel-Haenszel methods using fixed (if no heterogeneity) or random-effects model (I 2 > 40%) [38]. Heterogeneity was tested using chi-square and I 2 tests, and significance was tested using the Z test.…”
Section: Discussionmentioning
confidence: 99%